Examining entrepreneurial experience in relation to pre-launch and post-launch learning activities affecting venture performance. (4th July 2022) - Marvel, Matthew R.; Wolfe, Marcus T.; Kuratko, Donald F.; Fisher, Greg
ABSTRACT: Entrepreneurship research distinguishes between prelaunch learning in the form of customer and technology planning prior to launch and postlaunch learning in the form of product or market pivots after entry. We examine entrepreneurial experience as important to entrepreneurial learning by testing a model connecting entrepreneurial experience with prelaunch learning which, in turn, relates to postlaunch pivots and venture performance. Drawing from a sample of technology entrepreneurs, we found entrepreneurial experience is related to prelaunch learning in both the customer and technology domains. Prelaunch learning in the customer domain has a negative association with market pivots, which negatively relates to venture performance.